Chronic nitrogen legacy in the aquifers of China - Xin Liu; Fu-Jun Yue; Li Li; Feng Zhou; Hang Wen; Zhifeng Yan; Lichun Wang; Wei Wen Wong; Cong-Qiang Liu; Si-Liang Li (Communications Earth & Environment)
Abstract About half of the global drinking water comes from groundwater, yet groundwater quality is threatened by high nitrate concentrations globally. Our understanding of groundwater nitrate concentrations is often limited by inaccessibility of groundwater and scarcity of nitrate data in groundwater. Here we used machine learning and decision tree-heatmap analysis by compiling nitrate concentrations and isotope data from 4047 groundwater sites across China to understand their dynamics and drivers across gradients of geographical, climate, and human factors. Results show that nitrate concentrations vary substantially over depth and are generally lower in deeper groundwater, indicating potentially higher nitrate removal rates according to nitrate isotopic pattern such as denitrification at depth. At similar groundwater aquifer depths, nitrate concentrations are highest in urban regions with high population density. In addition, nitrate concentrations are generally higher in arid northern China than humid southern China. Interestingly, while groundwater nitrate concentrations are lower at deeper depths, slow groundwater flow also indicates prolonged nitrogen legacy. Although there has been an overall decline in groundwater nitrogen pollution in China since 2016, persistent pollution has lingered. Future strategies for groundwater quality protection in China should address the long-term legacy of nitrate in different aquifers and rising nitrogen levels in groundwater.